Local and sustained miRNA delivery from an injectable hydrogel promotes cardiomyocyte proliferation and functional regeneration after ischemic injury - Wang, Leo L. (Nat Biomed Eng, 2017)
MicroRNA-based therapies that target cardiomyocyte proliferation have great potential for the treatment of myocardial infarction (MI). In previous work, we showed that the miR-302/367 cluster regulates cardiomyocyte proliferation in the prenatal and postnatal heart. Here, we describe the development and application of an injectable hyaluronic acid (HA) hydrogel for the local and sustained delivery of miR-302 mimics to the heart. We show that the miR-302 mimics released in vitro promoted cardiomyocyte proliferation over one week, and that a single injection of the hydrogel in the mouse heart led to local and sustained cardiomyocyte proliferation for two weeks. After MI, gel/miR-302 injection caused local clonal proliferation and increased cardiomyocyte numbers in the border zone of a Confetti mouse model. Gel/miR-302 further decreased cardiac end-diastolic (39%) and end-systolic (50%) volumes, and improved ejection fraction (32%) and fractional shortening (64%) four weeks after MI and injection, compared to controls. Our findings suggest that biomaterial-based miRNA delivery systems can lead to improved outcomes in cardiac regeneration.